Role of Radiology and Laparoscopy in Childhood Peptic Ulcer Perforation. (20th July 2022) - Demir, Mesut; Akın, Melih; Yücel, Nurdan; Unal, Aydin; Gürel, Duygu; Yaşa, Eren
Abstract : Objective . Peptic ulcer disease (PUD) in children is an uncommon disorder. An estimated 1.3 percent to 20 percent of people die from perforated peptic ulcers (PPU), a PUD consequence. Using a database, we assess the prevalence and prognosis of PPU in patients. We also do radiological and laparoscopic operations for PPU in young patients. In pediatric patients, sufficient accumulation of knowledge about laparoscopic repair is at the level of case reports. This study aims to assess the results in pediatric cases operated for PUP by open or laparoscopic surgery and determine the role of computed tomography (CT) in diagnosing PUP. Methods . Data was collected from the Department of Pediatric Surgery, Sisli Hamidiye Etfal Training and Research Hospital, Turkey, from 2015 to 2020. Patients under 18 years of age who were operated on for PUP between 2015 and 2020 were divided into two groups. Group 1 involved those patients operated by laparoscopic surgery, whereas Group 2 involved those used by open surgery. Both groups were retrospectively evaluated in terms of demographic data, clinical findings, preoperative-intraoperative findings and surgical methods (open or laparoscopic), duration of surgery, duration of nasogastric intubation, time of return to oral feeding, length of hospital stay, and postoperative complications. Results . 18 patients consisting of 15 boys and 3 girls were included in the study. Group 1 involved 10 patients, whereas Group 2 involved 8 patients. In Group 1, the symptom onset period was 1.6 ± 1.9 days, and in Group 2, it was 6.6 ± 6.1 days. In the erect abdominal radiographs (AXR) of 10 (58.8%) patients, the air was under the diaphragm. Six patients whose erect AXRs showed no attitude under the diaphragm but had abdominal pain and acute abdominal manifestation were given abdominal computed tomography (CT) scanning. In all patients with PUP, laparoscopic/open surgery involves primary suturing and repair by omentoplasty (Graham patch). The mean operative time was 87.0 ± 26.3 minutes in Group 1 and 122.5 ± 57.6 minutes in Group 2. The mean length of hospital stay was 3.9 ± 1.3 days in Group 1 and 5.8 ± 2.1 days in Group 2. Neither group developed any major surgical complications. Conclusions . Adolescents with a history of sudden onset and severe abdominal pain may present with peptic ulcer perforation even if there is no known diagnosis of peptic ulcer or predisposing factor. In cases suspected of PUP, it is vital to order and carefully examine erect AXR, which is an easy and inexpensive method. Computed tomography should be the first choice in patients without free air in ADBG but whose anamnesis and findings match peptic ulcer perforation.